A framework to develop an e-commerce strategy selling products online for agriculture manufacturers - Goodman, Brett (Kansas State University, 2015)
E-commerce is changing the purchase habits of businesses, globally. The potential for agricultural input manufacturers to develop an online business-to-business (B2B) model may provide a new source of revenue by reaching an underserved market. Underserved markets are those which a company’s primary brand is not reaching a certain customer base. The following thesis was conducted for a client (Company A) to determine the feasibility of increasing one point of market share in corn seed through an online and phone based sales model. In recent years, consolidation among agricultural seed companies, along with product performance, has driven swings in market share. Gaining one point of market share in corn seed is equivalent to 376,000 units. Company A believes there is opportunity to gain one percentage point of share in the corn seed industry through online and phone-based sales. FC, an online and phone based seed company, held approximately one percentage point of share before being purchased by Company B in 2007. Company B then retired the FC brand in 2012. FC was once successful in their e-commerce based strategy; however three dominant factors impacted the development of agriculture companies conducting business online. Those factors are: 1) industry structure, 2) product complexity, and 3) the hightouch nature of transactions in agriculture. Research regarding e-commerce in agriculture has been limited over the past few years. With the increase in Internet access through wireless modems and mobile broadband data plans, opportunity exists for agricultural businesses to develop e-commerce B2B marketing. Research reported here focused on exploring the feasibility of selling a corn seed brand online and by phone, only. The steps to address the feasibility were to identify the target market and market opportunities and, then, address opportunities and challenges a company could face developing such a business.
Keywords: E-commerce; Agriculture